Calcification in cerebral parenchyma affects pharmacoresistant epilepsy in tuberous sclerosis. (August 2018) - Zhang, Meng-Na; Zou, Li-Ping; Wang, Yang-Yang; Pang, Ling-Yu; Ma, Shu-Fang; Huang, Lu-Lu; Gao, Yang; Lu, Qian; Franz, David Neal
Highlights: mTOR inhibitors have effect on controlling epilepsy in TSC. Calcification in epileptic foci strongly suggested drug-resistant epilepsy in TSC. CT was also of value in evaluating pharmacoresistant epilepsy in TSC. Abstract: Purpose: Tuberous sclerosis (TSC) is an autosomal dominant inherited disease caused by mutations in the TSC1 or TSC2 gene and results in the over-activation of the mammalian target of the rapamycin (mTOR) signaling pathway. Rapamycin, an mTOR inhibitor, is clinically used to treat hamartomatous lesionsas in TSC and its effect on controlling epilepsy is also reported in many studies. This study aims to evaluate the risk factors of pharmacoresistant epilepsy in patients with TSC receiving long-term rapamycin treatment. Method: A total of 108 patients with TSC taking rapamycin for over 1 year were enrolled in this study. Factors that might influence seizure control were statistically analyzed by multiple factor analysis. A subgroup analysis was also conducted to access the relationship between calcified epileptic foci and pharmacoresistant epilepsy. (Clinical trial registration number: ChiCTR-OOB-15006535(2015-05-29)). Results: Seizure was controlled in 53 patients but was not managed in 55 patients considered to be drug resistant. Logistic regression analysis showed that calcification in the cerebral parenchyma was a risk factor of pharmacoresistant epilepsy [P = 0.006, odds ratio (OR) = 4.831 (1.577, 14.795)]. Fifteen of 17 patients with calcified epileptic foci suffered from pharmacoresistant epilepsy (88.2%). Seizures in patients with calcified epileptic foci were probably pharmacoresistant (P = 0.010). Conclusion: Calcification in epileptic foci strongly indicates pharmacoresistant epilepsy in patients with TSC even when treated with appropriate anti-epilepsy drugs (AEDs) and rapamycin. Calcification can be used to evaluate pharmacoresistant epilepsy in patients with TSC.